2021
DOI: 10.1038/s41598-021-83518-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of full-length ureter defects by laparoscopic bladder flap forming

Abstract: To evaluate the safety and efficacy of laparoscopic bladder muscle flap reconstruction in the treatment of extensive ureteral avulsion. Patients with full-length (re length > 20 cm) and upper ureteral (avulsion length > 10 cm) defects were eligible. All patients were treated with laparoscopic bladder muscle flap reconstruction. Peri-operative information and post-operative complications were recorded. The kidney function, urinary ultrasound or computed tomography (CT), sun-renal function tests emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(4 reference statements)
0
8
0
Order By: Relevance
“…However, it may reduce bladder capacity and is ineffective for longer ureteral defects (more than 15 cm). 14 In our case, the defect was in the med ureter, the procedure was successful, and postoperative bladder capacity and ureteral caliber were acceptable.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, it may reduce bladder capacity and is ineffective for longer ureteral defects (more than 15 cm). 14 In our case, the defect was in the med ureter, the procedure was successful, and postoperative bladder capacity and ureteral caliber were acceptable.…”
Section: Discussionmentioning
confidence: 54%
“…Psoas bladder hitch, ureter replacement, renal auto-transplantation, Boari flap, and nephrectomy are all suggested surgical procedures. 14 Boari flap procedure is usually used in affected distal or mid ureter without needing bowel segment resection or bladder augmentation. However, it may reduce bladder capacity and is ineffective for longer ureteral defects (more than 15 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Boari bladder flap is usually used for bridging long defect up to 15cm 20 , 21 . Bai et alreported their laparoscopic reconstructive experience with bladder muscle flap for treating full-length ureteral defect, and the longest length was 21 cm 22 . In our study, the median defect length was 6 cm, ranging from 5 to 17 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with open surgery, laparoscopic reconstructive technique superior in terms of less blood loss, fewer complications, and better cosmetic outcomes 1 , 23 . Numerous studies have demonstrated satisfactory outcomes and acceptable complications of laparoscopic bladder flap surgery 21 , 22 , 24 , 25 . Laparoscopy has specificities of magnifying effect and extremely clear vision, which could avoid excessive dissection of the healthy ureter, achieve effect of mucosa -mucosa anastomosis and maximize protection of the ureteral blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…The anastomotic stoma was covered with the greater omentum during the operation. Not only can the greater omentum reduce the occurrence of urine leakage, but its blood supply can also increase the nutritional supply of the anastomosis and reduce the chance of necrosis and stenosis (18). The laparoscopic onlay of LMG ureteroplasty combined with ureterovesical reimplantation for one-stage reconstruction of unilateral complex ureteral strictures, as compared with traditional IUR and kidney autotransplantation, shortens the operation time and reduces the incidence of complications, which is beneficial to the rapid recovery of patients after operation.…”
Section: Discussionmentioning
confidence: 99%